2019
DOI: 10.3390/foods8110585
|View full text |Cite
|
Sign up to set email alerts
|

Spent Coffee Waste as a Potential Media Component for Xylanase Production and Potential Application in Juice Enrichment

Abstract: In this study, spent coffee waste (SCW) was used as the sole carbon source for xylanase production in solid state fermentation mode using Aspergillus niger. A Box–Behnken design was constructed using three parameters viz. temperature, initial moisture content, and log number of spores to determine the optimal fermentation condition. The best fermentation conditions for xylanase production were found to be incubation at 30 °C with an initial moisture content of 70% and using an inoculum of 6.5 × 106 spores/g of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 35 publications
(44 reference statements)
1
13
0
Order By: Relevance
“…A xylanase produced from Aspergillus niger was purified, and investigated for its fruit juice clarification potential of various fruits like strawberry, blueberry, and raspberry pulp [23]. Similar to the current study, enzyme dosage, temperature and time of enzyme treatment, were earmarked as the most vital variables which influenced the clarification of fruit juices.…”
Section: Doe Based Optimization Of Orange and Mosambi Juice Clarificasupporting
confidence: 64%
See 3 more Smart Citations
“…A xylanase produced from Aspergillus niger was purified, and investigated for its fruit juice clarification potential of various fruits like strawberry, blueberry, and raspberry pulp [23]. Similar to the current study, enzyme dosage, temperature and time of enzyme treatment, were earmarked as the most vital variables which influenced the clarification of fruit juices.…”
Section: Doe Based Optimization Of Orange and Mosambi Juice Clarificasupporting
confidence: 64%
“…SSF was executed for xylanase production by cultivating Aspergillus niger on spent coffee waste as the sole carbon source. Various process parameters were optimized using a Box-Behnken design to achieve 1.39-fold increased xylanase yield [23]. Similarly, spent mushroom substrate of Pleurotus florida was employed as the substrate for SSF based production of lignocellulolytic enzymes such as cellulases and xylanases using species of Trichoderma and Aspergillus [21].…”
Section: Xylanase Production From a Terreus S9 Using Various Agroindmentioning
confidence: 99%
See 2 more Smart Citations
“…Coffee husk (CH) is a coffee waste with interlinked complex molecular structure of lignocellulose materials like cellulose, hemicellulose, and lignin. [30][31][32] Recently, sustainable PBS biocomposites have been fabricated using spent coffee waste as a renewable source to lower the cost of production. Results also showed that such composites can degrade twice as fast and exhibit higher stiffness than neat PBS.…”
mentioning
confidence: 99%